Heterogeneity of Radiological Spectrum in Tacrolimus-Associated Encephalopathy after Lung Transplantation - Qisi Wu; Christian Marescaux; Xinyue Qin; Romain Kessler; Jun Yang (Behavioural Neurology)
Background. Tacrolimus-associated encephalopathy (TAC-E) is usually described under the term of posterior reversible encephalopathy syndrome (PRES). However, a large amount of data has suggested that TAC-E is not a homogenous entity: indeed, TAC-E which is often presented with atypical and potentially misleading imaging characteristics does not always correspond to PRES. Objective. We aimed to identify the spectrum of brain MR imaging of TAC-E and discuss the underlying pathophysiological features. Methods. From September 2008 to October 2010, the neurological statuses of 45 patients, who underwent lung transplantation with TAC as posttransplantation immunosuppressive therapy, were regularly assessed in a prospective study. MRI was repeatedly performed, until recovery, in patients who developed central neurological symptoms. Results. Symptoms suggestive of encephalopathy occurred in five out of 45 patients (11.1%). According to our MRI study, two patients presented with reversible bilateral and relatively symmetric subcortical white matter edema with proximal vasospasms on MRA; however, three other patients were characterized by coexistence of two different lesions including laminar cortical infarcts with hemorrhagic transformation not typically found in PRES and reversible deep white matter edema, associated with distal vasospasms on MRA. Conclusions. It is considered that the mechanism of TAC-E would be more heterogenous than commonly perceived.